Revisiting the water issue across the causeway: the origins of water supply from Johor To Singapore (1904-32) - A, Rahman Tang Abdullah (Penerbit UKM, 2013)
This article discusses the origins and historical development of the water supply between Johor and Singapore from 1904 to 1932. It reveals the events that preceded the formative stages of the water-supply scheme; analyses the 1927 water agreement and its implications; and examines the dynamics of water supply to Singapore before the Second World War. It demonstrates that the political framework underpinning the supply of water between the two countries has been determined in favour of Singapore as a matter of colonial legacy. Singapore has traditionally enjoyed a strategic advantage over Johor because the former was more developed, a fact that resulted in part from the British authorities’ prioritisation and promotion of the island as the seat of their imperial power in Southeast Asia during the nineteenth and twentieth centuries. As a result, Singapore flourished, becoming more prosperous than her neighbouring states by generating surplus revenue from their economic resources on the strength of their capitalist framework. Consequently, Singapore was able to exploit the water deal to her advantage during the colonial period. Despite the importance of the water deal in the two countries history, it has not been discussed by historians whose writings tend to focus on water issues post-1961.